2009
DOI: 10.1016/j.cct.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a palm pilot intervention for primary care providers: Lessons learned

Abstract: The Personal Digital Assistance for Guideline Adherence (GLAD Heart) study was designed to test a strategy to improve quality of care through increased adherence to ATPIII cholesterol guidelines. This paper describes the overall study design including the multi-faceted intervention and outcome measures. Sixty-one primary care practices in NC were recruited and randomized to either a personal digital assistant-based cholesterol management intervention or an intervention similar in intensity and frequency of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Eleven trials (17%) were published prior to 2000 [77-89], 16 (25%) trials [58,60-76] between 2000 and 2004 and 38 (58%) trials [16-57,59] after 2004. Most studies (n = 41, 63%) [16-21,23,24,26,28,31-33,38,40,42-44,47,48,55-57,60,61,63,66-68,70,72-80,82-88] reported public funding; nine (14%) [29,34,35,45,46,49,50,52,53,59,71] reported private funding; six (9%) [22,36,37,41,54,64,65,69] reported public and private funding, and 9 (14%) [25,27,30,39,51,58,62,81,89] did not disclose a funding source (see Additional file 3, Table S3). We were able to determine whether improvement occurred with a CCDSS for process of care outcomes in 59 studies [16-24,26-38,40-70,72-76,80-83,85-87,89]; 29 studies reported patient outcomes [19,25,26,29,33,38,39,43,45,48,49,51-53,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven trials (17%) were published prior to 2000 [77-89], 16 (25%) trials [58,60-76] between 2000 and 2004 and 38 (58%) trials [16-57,59] after 2004. Most studies (n = 41, 63%) [16-21,23,24,26,28,31-33,38,40,42-44,47,48,55-57,60,61,63,66-68,70,72-80,82-88] reported public funding; nine (14%) [29,34,35,45,46,49,50,52,53,59,71] reported private funding; six (9%) [22,36,37,41,54,64,65,69] reported public and private funding, and 9 (14%) [25,27,30,39,51,58,62,81,89] did not disclose a funding source (see Additional file 3, Table S3). We were able to determine whether improvement occurred with a CCDSS for process of care outcomes in 59 studies [16-24,26-38,40-70,72-76,80-83,85-87,89]; 29 studies reported patient outcomes [19,25,26,29,33,38,39,43,45,48,49,51-53,…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Additional file 2, Table S2, the majority of CCDSS systems in our sample were integrated with an EMR (n = 38/61, 62%) [17,18,20,23-26,28,31,32,34,40,42,44-47,49,55,56,58-66,68-70,73,74,77-85,87,89], delivered feedback via a computer display (n = 44/62, 71%) [17,18,20,23-26,28,30-36,38-40,42,44,46-49,51,55-58,60-66,68-71,73-76,80,82-84] at the time of care (n = 53/64, 83%) [16-21,23-26,28,30-35,38,40,42,44,46-51,53,55-58,60-70,72-85,87-89]. A minority of authors reported testing a CCDSS with a graphical user interface (n = 22/25, 88%) [16-18,20,21,23-25,28,30,31,34,38,40,45,46,55,56,58-60,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Providers were able to obtain second opinions on complicated cases and advice from specialists not stationed at their base. Digital technology including electronic patient health portals, apps and social media will be a key player in shaping adherence behavior, by making more data available for a more insightful understanding of patient adherence and decision-making [13]. The digitalization of health records alone will facilitate data sharing across providers and provide detailed information about patient adherence, along with demographic data, medical history and current precipitating factors.…”
Section: Digital Technologymentioning
confidence: 99%